2016
DOI: 10.1074/jbc.m116.749515
|View full text |Cite
|
Sign up to set email alerts
|

Binding Sites for Acylated Trehalose Analogs of Glycolipid Ligands on an Extended Carbohydrate Recognition Domain of the Macrophage Receptor Mincle

Abstract: The macrophage receptor mincle binds to trehalose dimycolate on the surface of Mycobacterium tuberculosis. Signaling initiated by this interaction leads to cytokine production, which underlies the ability of mycobacteria to evade the immune system and also to function as adjuvants. In previous work the mechanism for binding of the sugar headgroup of trehalose dimycolate to mincle has been elucidated, but the basis for enhanced binding to glycolipid ligands, in which hydrophobic substituents are attached to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 36 publications
7
80
0
Order By: Relevance
“…A common Mincle ligand signature structure has been predicted based on a number of identified ligands (6,7,(33)(34)(35) in combination with the Mincle protein structure (9)(10)(11)(12). A polar head consisting of glucose or mannose and a hydrophobic chain appear to be the minimum requirement for ligand activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common Mincle ligand signature structure has been predicted based on a number of identified ligands (6,7,(33)(34)(35) in combination with the Mincle protein structure (9)(10)(11)(12). A polar head consisting of glucose or mannose and a hydrophobic chain appear to be the minimum requirement for ligand activity.…”
Section: Discussionmentioning
confidence: 99%
“…All six β-GlcCer species examined in this study satisfy these criteria as they harbor a polar glucose head and two acyl chains within the ceramide moiety. It remains unclear why the unsaturated β-GlcCer C24:1(15Z) possesses the most potent ligand activity, as the crystal structure of Mincle (9,10,12) suggested that the double bond of C24:1 is likely to be located away from the Mincle interacting site. Cocrystallization of Mincle protein and β-GlcCer C24:1 should clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, structural, binding, and mutagenesis data support a model for TDM and TDB binding in which the two glucose units and also, surprisingly, one acyl chain interact directly with the CRD of Mincle (8,13,15). The precise molecular mechanisms of the glycolipid-Mincle interaction are far from being completely understood, particularly with respect to how the two complex MAs of TDM are recognized by the receptor.…”
mentioning
confidence: 98%
“…These structural regions were previously found to adopt different conformations in the crystallized forms of human Mincle (14) compared with the bovine Mincle (13). Moreover, it has been suggested that the conformation of the loop between residues N170 and D177 could play a key role in the ability of Mincle to bind to the glycolipid (15,25).…”
Section: Deciphering the Structural Features Required For (Glyco)lipidmentioning
confidence: 99%